Analisis Pengaruh Promosi Penjualan, Kemudahan dan Kepercayaan Terhadap Keputusan Pembelian Pada E-Commerce Shopee - Nabilah Rahmani (2021)
Analysis of the Effect of Sales Promotion, Ease of Use and Trust on Purchase Decisions at E-Commerce E-Commerce By Nabilah Rahmani Abstract The increasing number of internet users has changed people's behavior in Shopping. In the past, if people wantes to shop, people had to come directly to offline stores, but with e-commerce, people can shop online anythime and anywhere. In Indonesia, e-commerce competition is so tight that e-commerce companies take various ways to become the user's first choice. Currently Shopee is the most visited marketplace in Indonesia since the 4th quarter 0f 019 until now. This research is a quantitative study that aims to determine the effect of promotion, ease of use and trust on purchasing decisions at e-commerce Shopee. The population in this study are Shopee e-commerce users who live in Jakarta. The sample size was taken as many as 75 respondents, with non-probability sampling technique used is purposive sampling. Data was collected through the distribution of online questionnaires using google form. The analysis technique uses Partial Least Square (PLS) with smartPLS 3.0 software. The results showed that (1) Sales promotion had a positive and significant effect on purchasing decisions. (2) Ease of use has a positive and significant effect on purchasing decisions. (3) Trust has a positive and significant effect on purchasing decisions Keyword : Sales promotion, Ease of Use, Trust, Purchase Decision